Experimental study on elastic-plastic seismic response analysis of concrete gravity dam with strain rate effect. Issue 116 (January 2019) - Hai-tao, Wang; Jiayu, Shen; Feng, Wu; Zhiqiang, An; Tianyun, Liu
Abstract: Combined with the plasticity - damage constitutive model of hydraulic concrete obtained from the test by considering the strain rate effect, the elastic-plastic numerical simulation of Koyna concrete gravity dam under different seismic waves is carried out with ABAQUS software. The effect of strain rate on the dynamic performance of concrete gravity dam under earthquake is discussed by comparing the results of high strain rate and quasi-static loading. The results show: when the peak acceleration is small, the acceleration and displacement of the feature point calculated by considering the strain rate effect are smaller than those without considering the strain rate effect, and the difference is not obvious. With the increase of the seismic peak acceleration, the difference gradually increases. Considering the effect of concrete strain rate, the principal tensile stress in the dam is higher than without considering the strain rate, and more in accordance with the actual damage form. It is suggested that the strain rate effect of concrete should be considered in the seismic response analysis of concrete gravity dam. Highlights: The plasticity-damage constitutive model of hydraulic concrete is obtained. The elastic-plastic numerical simulation of Koyna concrete gravity dam is carried out with ABAQUS software. The effect of strain rate on the dynamic performance of concrete gravity dam under earthquake is discussed.